INTEGRATION OF THE USER SATISFACTION MODEL METHOD IN MEASURING WEBSITE QUALITY - Khairul Fikri (DiJITAC : Digital Journal of Information Technology and Communication, 2026)
As digital presence becomes mandatory for educational institutions, ensuring website quality through systematic measurement is vital. This study investigates the Website of the Faculty of Science and Technology (FSAINTEK) at UIN Datokarama Palu, which had not undergone any formal quality assessment since its active management began in 2025. The research objective is to evaluate user satisfaction and identify critical improvement areas using an integrated measurement framework. This research proposes the integration of variables from three established models: User Satisfaction, End-User Computing Satisfaction (EUCS), and Webqual 4.0, covering Ease of Use, Customization, Download Delay, Content, and Service Interaction Quality. Utilizing a descriptive quantitative method with 53 diverse respondents, the data underwent validity, reliability, and score interpretation analysis. The findings reveal a global satisfaction index of 79.53%, classified as "Strong." However, a significant "retention paradox" was discovered: while accessibility scored 84.91%, the frequency of visits remained low at 67.17%. The primary contribution of this research is the holistic 360-degree perspective it offers, highlighting that technical excellence alone is insufficient without dynamic content updates. Unlike traditional single-model evaluations, this integrated approach successfully identifies the disconnect between technical functionality and user engagement. The study concludes that to reach higher satisfaction levels, the faculty must transition from technical-oriented maintenance to a value-driven content strategy, emphasizing the necessity of periodic content audits and file optimization to bridge the engagement gap.